Fiscal capacity and social protection expenditure in developing nations - Syed Mansoob Murshed; Muhammad Badiuzzaman; Mohammad Habibullah Pulok (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
There is scant analysis on the causal relationship between fiscal capacity and social protection expenditure in the developing world. We investigate the causal relationship between fiscal capacity of the state and social protection expenditure, hypothesizing that fiscal capacity is necessary but not sufficient for resource allocation in this area. Using a panel data instrumental variable approach, we find that greater fiscal capacity robustly raises social protection spending in developing countries between 1990 and 2010, providing strong evidence for social sector spending being augmented by enhanced fiscal capacity in the presence of a well-functioning democracy.
Keywords: H51; H55; H62; O11; 330; fiscal capacity; inequality; institutions; social protection expenditure